ANALISIS WACANA KRITIS MEDIA ONLINE “NIA GADIS PENJUAL GORENGAN” - Ayesha Nazara Prameswari; Hilma Erfiani Baroroh (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to analyze the text structure, social cognition, and social context in online media about Nia, a girl selling fried food who was a victim of rape and murder. The main focus of this study is to reveal how the media constructs and conveys information about the incident using a critical discourse analysis approach, especially Teun A. Van Dijk's theory. The method used is descriptive qualitative with data collection techniques through reading and recording news from two online media sites, namely detik.com and tvonenews.com, which contain the chronology of events. The results of the study show that although both news stories have the same theme regarding the development of the rape and murder case, there are differences in the content of the two news stories. The discourse structure in the news stories reveals how the media constructs narratives with the aim of shaping readers' perceptions, especially in highlighting the role of the police and describing the perpetrator's crimes. In addition, this analysis identifies discourse elements that reflect the dynamics of power underlying the news.